Lack of vascular adventitial fibroblastic cells in tumour stroma of intestinal-type and solid-type gastric carcinomas. Issue 2 (27th January 2004) - Nakayama, H; Enzan, H; Miyazaki, E; Kuroda, N; Toi, M; Hiroi, M; Yasui, W
Abstract : Aims: To investigate the roles of vascular adventitial fibroblastic cells in tumour stroma, the distribution of vascular adventitial fibroblastic cells was studied in gastric carcinomas. Methods: In total, 50 surgically resected gastric carcinomas (43 intestinal type, and seven solid type) and their normal tissues were examined. Vascular adventitial fibroblastic cells are positive for CD34 but negative for CD31. To differentiate vascular adventitial fibroblastic cells from vascular endothelial cells, immunostaining for CD34 and CD31 was performed. Immunostaining for high molecular weight caldesmon was also performed to recognise vascular media. Results: In normal gastric tissues, CD34 positive fibroblastic cells were found just outside the vascular media, namely vascular adventitial fibroblastic cells. In contrast, all of the 43 intestinal-type and seven solid-type gastric carcinomas had no vascular adventitial fibroblastic cells in the tumour stroma. Conclusions: These results suggest that a lack of vascular adventitial fibroblastic cells is associated with tumour stroma formation in intestinal-type and solid-type gastric carcinomas.